Stemma og stilla i musikk og litteratur Festskrift til Magnar Åm - Hjorthol, Geir; Løvoll, Helga S.; Oltedal, Elizabeth; Sørbø, Jan Inge (Religionsfag Profil, 2022)
This book is in commemoration of the composer, educator, conductor and social worker Magnar Åm's 70th birthday. Right from the start of work as a composer, music as a form of recognition has been central, along with an impulse to disrupt boundaries between established forms and conventions. This has also been a guiding principle behind the contributions to this anthology, where the goal has not only been to honor one individual, but to be a source of new insight. Music and literature are about the creation and dissemination of meaning. In this sense, it is paradoxical to talk about silence as a hallmark of certain art forms. But anyone who reads or listens actively knows that there is more to be gained from art than what lies in the immediate and explicit expression. The voice (in a broad sense) finds its complimentary opposite in silence. The first part of the anthology provides a brief theoretical background for interdisciplinary research into music and literature. The contributions that follow do not view artworks simply as finished products, but as parts of a living practice in which the composer, author, music, text, performer and audience all meet. In the next part, we are drawn into the workshops of composers and musicians who reflect on the music of Magnar Åm, as well as their own in light of this. In the final part, we cross the border between art and other forms of experience, with eudaimonia as a unifying concept: How should one live a complete and meaningful life? This book has been written by researchers in a variety of fields such as literature, music, natural science and outdoor life, as well as practicing artists: composers, musicians and writers. Between research and art, through scientific articles and professional essays, a conversation arises that engenders recognition across fixed boundaries.